Strategic Planning of Information Systems to Improve the Quality of Business Processes at the University: Perencanaan Strategis Sistem Informasi untuk Meningkatkan Kualitas Proses Bisnis di Universitas - Eka Novita Sari; Isa Mulia Insan; Christian Susetyo Harjanto (Software Development, Digital Business Intelligence, and Computer Engineering, 2025)
Information Technology (IT) is one of the innovations that has been widely applied in various fields. In Indonesia, the field of education is currently implementing a lot of IT. However, IT owned by universities in Indonesia is still not used optimally. This happens because there is no strategic planning for the use of IT owned by the university. By optimizing the application of IT, universities can improve the quality of their business processes. This study will propose IS/IT strategic planning that can be applied to universities in Indonesia. To design the strategy, literature studies and observations were carried out to obtain the appropriate data. The data needed are in the form of the latest internal and external conditions from one of the universities in Indonesia. From the data that has been obtained, the processing is carried out with the framework that has been adopted. The output generated from all IS/IT strategic planning activities at the university is an IS/IT strategic planning document that contains several analysis results, such as the direction of the company's business development and the direction of development of Information Systems (IS) used to support the path of business development. In addition, IS recommendations based on business analysis results and IS trends have also been generated. The strategy for implementing IT has been designed based on the current situation so that the resulting strategy can be used as a reference for the implementation of IT at the university.